2008
DOI: 10.1002/jso.21114
|View full text |Cite
|
Sign up to set email alerts
|

A modified grading system for post‐hepatectomy metastatic liver cancer originating from colorectal carcinoma

Abstract: The simpler system of MGJSCCR is a better predictive grading system of prognosis of MLC patients who had undergone hepatic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
4
0
10
Order By: Relevance
“…Figure describes the search results. The scientific literature review and web‐based search identified 53 tools predicting survival in colon or rectal cancer, reported across 63 articles . Two articles reported on the development of two tools each .…”
Section: Resultsmentioning
confidence: 99%
“…Figure describes the search results. The scientific literature review and web‐based search identified 53 tools predicting survival in colon or rectal cancer, reported across 63 articles . Two articles reported on the development of two tools each .…”
Section: Resultsmentioning
confidence: 99%
“…This score would be useful in predicting shorter survival by our recent report. 32 Several recent reports indicate the usefulness of adjuvant chemotherapy in increasing the survival periods in CLM patients undergoing hepatectomy. 3,6,15,16 Postoperative adjuvant therapy and follow-up…”
Section: Comprehensive Grading System For Colorectal Liver Metastasismentioning
confidence: 99%
“…У хірургічних клініках нерідко виконують резекцію печінки, яка здійснюється при доброякісних і злоякісних пухлинах, метастазах, травмах печінки, внутрішньопечінковому холангіотіазі, альвеолярному ехінококозі, трансплантації печінки [1,2]. Резекція великих об'ємів печінки може призводити до різних ускладнень, зокрема, до портальної пострезекційної гіпертензії, при якій підвищується тиск крові у системі ворітної печінкової вени, печінкових венах, а також у нижній порожнистій вені [1,3,4]. Головними клінічними ознаками портальної гіпертензії є розширення і повнокров'я ворітної печінкової вени, брижових вен, варикозне розширення вен стравохода і шлунка, прямокишкових вен, вен передньої черевної стінки, шлунково-кишкові кровотечі, спленомегалія, асцит.…”
unclassified